Liquidity Provision in the Overnight Foreign Exchange Market - Geir Høidal Bjønnes; Dagfinn Rime; Haakon Solheim (Norges Bank, 2004)
We presents evidence that non-financial customers are the main liquidity providers in the overnight foreign exchange market using a unique daily data set covering almost all transactions in the SEK/EUR market over almost ten years. Two main findings support this: (i) The net position of non-financial customers is negatively correlated with the exchange rate, opposed to the positive correlation found for financial customers; (ii) Changes in net position of non-financial customers are forecasted by changes in net position of financial customers, indicating that non-financial customers take a passive role consistent with liquidity provision.
hdl:11250/2498541; Additional information: Also published in Journal of International Money and Finance, 2005, issue 2 (March 2005), pp. 177-198.
Keywords: F31; F41; G15; 330; microstructure; international finance; liquidity